Economic displacement and livelihood threats: The impact of industrial resource extraction on local economies - Bans-Akutey, Anita (Journal of Social, Humanity, and Education, 2025)
Purpose: This study seeks to deconstruct the complex factors underlying the conflict between local miners, the Ada East District Assembly, and Electrochem Ghana by applying a Political Ecology framework. Research methodology: A qualitative analysis and the Political Ecology theoretical lens are used to examine underlying factors of the case. It draws on empirical evidence from similar conflicts in the region; and contextualizes the Ada East situation within broader patterns of industrial resource extraction and their impact on local economies. Results: Two core theses of Political Ecology emerge as most relevant to the case: (1) Power and Access to Resources, which examines how control over natural resources by corporations can marginalize local people and (2) Environmental Justice, which highlights the disproportionate socio-environmental costs borne by local communities. Conclusions: This study concludes that the conflict between local miners, the Ada East District Assembly and Electrochem Ghana is deeply rooted in competing interests over resource control, governance dynamics, and socio-environmental inequalities, as illuminated through the lens of Political Ecology. Limitations: The analysis is limited to secondary data from comparable cases, which vary in contextual specifics. Contribution: The study contributes to the literature on Political Ecology by demonstrating how this framework can be applied to assess real-world conflicts over resource access and industrial expansion. It also emphasizes the importance of equitable governance and sustainable resource management in mitigating such conflicts.